Dientes incluidos ¨kissing Molar¨. Revisión sistemática - Carrillo Cumbicus, Leonardo Ismael (2024)
The condition known as "kissing molars", in which impacted molars have close contact between their occlusal surfaces and opposing roots, is relatively rare. A literature review is conducted to investigate the prevalence of this condition and the associated treatment options. Through a comprehensive search of electronic databases such as PubMed, SciELO, Cochrane, Redalyc, Scopus Preview, Elsevier, Dialnet and Google Scholar using various keywords including "kissing molars", "beso de molares" and "molares incluidos", the study identified 21 cases of "kissing molars". The findings indicate that 63.2% of these cases recommend surgical extraction as the preferred treatment, while 15.7% included maintenance, and 21.1% mentioned orthodontic therapy. In terms of gender prevalence, it is more common in males (76.2%) than in females (23.8%). Furthermore, "kissing molars" are predominantly diagnosed in adults (aged 27 to 59 years, 61.9%), with adolescents and young adults accounting for 19.01% each. In conclusion, surgical extraction emerges as the primary treatment choice, while age and gender do not appear to be predisposing factors for this condition